Effect of Exercise Imagery and Self Talk on Paralayang Sports - Moh Sholekhul Hadi; Muchsin Doewes; Sapta Kunta Purnama (Kazimierz Wielki University, 2019)
This research is motivated by psychological problems when the competition is of course a work that needs to be addressed so that young athletes have strong mentality during the competition, the right method of mental training is expected that young athletes already have mental steel early on. The purpose of this study was to determine the differences in the influence of mental imagery and self talk training methods on the results of landing accuracy in paragliding sports. This type of research is an experiment with division into 2 groups. The population in this study were 18 athletes. Sampling technique with total sampling. Data retrieval technique is by landing accuracy test. Data analysis techniques using ANAVA. The results of this study indicate differences in the results between the initial test with the final test, as shown in the table the results of the increase in the Self Talk method group which amounted to 87% is not better than the increase in the Imagery method group which has an increase of 96%. It can be concluded that there is a significant difference in the effect of mental training on Landing Accuracy Results. The Imagery training method gives a better effect than the Self Talk method.